Giordano Bruno and the copernican revolution - Ceballos Melguizo, Ramiro (Estudios de Filosofía, 1993)
The text tries to show those traits pointing to a relationship between Bruno’ s cosmological work and the cultural and historical event known as the Copemican Revolution. It is centered on a first stage documenting the relations between infinitism and copemican astronomy. The horizon of argument is constituted by the intention of placing Bruno’ s thinking among the first theoretical contributions to modemity.